Rural entrepreneurship and Innovation: some successful women's initiatives - Lúcia Pato (European Regional Science Association (ERSA), 2015)
Although rural entrepreneurship is an emergent field of study and has emerged as one of the most noticeable ways to promote rural development, the few studies concerning the theme are still incipient. Moreover, a lot of studies focus on farmers and rural entrepreneurs as a whole and little research emphasises women?s entrepreneurship, particularly in Portugal. Thus, this study explores entrepreneurial initiatives conducted by women in one of the most peripheral areas of Portugal - Montemuro (municipality of Castro Daire), where subsistence agriculture continues to be the main economic activity. These women have been stimulated to develop entrepreneurial activity in the countryside, taking advantage of local and endogenous materials (flax and wool) and traditional knowledge that through for generations mothers passed orally to daughters. Indeed, these women who have continually been working this type of materials in their homes, putting into practise what they have learnt from their grandmothers and mothers, began to create innovative and fashionable products. The aim of this study, therefore, is to explore womens entrepreneurship in rural communities of Montemuro region, raise awareness of the role that these women play in rural development and identify some strategic considerations towards the development of their work. Concerning methodological procedures, in addition to the collection of data and news from newspapers and visits on internet pages about these women?s work, this paper is based on exploratory visits in the study communities of the Montemuro region and in the technique of observation. Apart from this, an interview was conducted in one of the organizations of women. The results of the study point out that the women of Montemuro try to not only create their own work, but also keep the culture and local traditions alive, therefore contributing to rural development. However several difficulties in the development of these entrepreneurial initiatives persist and further progress must be made. According to this, rural and local resources should be seen as valuable and entrepreneurial actions must be continually supported in order to contribute towards a process of rural development. Governmental and other institutional support should be directed to these women entrepreneurs in areas which they have lack of knowledge and expertise and conduct to the creation of a culture of entrepreneurship in the local context. Moreover, the success of entrepreneurship actions depends on the cooperation and creation of networks among the different actors that live in the rural communities. In terms of limitations we emphasize the exploratory nature of the study. Thus in order to understand behaviours and attitudes of these women entrepreneurs, limitations and opportunities of their entrepreneurial actions, an in-depth study will be interesting, maybe in the form of a study case.
Keywords: L26; R11; 330; Rural entrepreneurship; Innovation; Woman; Rural development